Defining and conceptualizing impact investing: attractive nuisance or catalyst? - Hockerts, Kai (Journal of business ethics, 2022)
This introduction to the special issue on impact investing applies the attractive nuisance notion to impact investing. Social sector actors ‘trespassing’ on the playing field of conventional investment markets may not appreciate the risks. We apply the framework of essentially contested concepts to foster fruitful diverse research in this emerging research field. We advance six dimensions (intentionality, additionality, contribution, materiality, measurability and attribution), which we propose allow to describe different sub-clusters of how the term is used in research and practice. For each dimension we identify risks and opportunities stemming from the contested nature and highlight an ambitious research agenda for how future business ethics scholars can help address and foster impact investing. We conclude by illustrating how the papers in this special issue address these challenges.